A Comparative Study of Character Development of Nature-Loving Students in Green Zone and Mayapada in Sumenep Regency - Kasim Solah Abubakar; Bagus Amirullah (Comprehensive: Jurnal Ilmu Pendidikan dan Keguruan, 2026)
This study compares student character development in MAPALA Green Zone Al-Amien Prenduan University and MAYAPADA STKIP PGRI Sumenep. With a qualitative approach and Comparative Study Method, data were collected through interviews, observations, and document analysis of 14 informants, including members, administrators, and seniors. Sampling techniques used are purposive and cluster sampling. The results showed that MAPALA Green Zone emphasizes character building through hands-on experiences, such as intense physical training, Islamic mentoring, and routine evaluations, with a focus on discipline, responsibility, solidarity, and leadership. Meanwhile, MAYAPADA STKIP PGRI Sumenep applies a holistic approach that includes physical, mental, social, and emotional aspects through programs such as DIKLATSAR and Dies Maulidiyah. Although the methods differ, both organizations are effective in shaping the character of members. Strategy differences are influenced by institutional context, vision, and organizational culture. These findings can be a reference for similar organizations in designing character development programs.